Heart Rate Variability Modulates the Relationship between Anxiety Symptoms and Emotional Responses to Anxiety-Provoking Imagery: A Cross-Sectional Study - Andronikos Strouthos; Elena Constantinou; Chrysanthi Leonidou; Maria Karekla; Georgia Panayiotou (Heart and Mind, 2025)
Background: Anxiety disorders have traditionally been related to low heart rate variability (HRV), whereas high HRV has been related to mental health and effective emotion regulation. This study examined if HRV indices of parasympathetic control of the heart are related to emotional responses of anxious individuals to anxiety imagery scenes, in a community sample. Methods: A total of 101 participants from the Cyprus Republic community, with a mean age of 28.3 years (18.8% males), were included in the study. Of these participants, those who did not meet screening criteria for anxiety disorders, based on self-report measures, were assigned to the control group (n = 55), while those meeting anxiety disorder criteria were assigned to the anxiety group (n = 30). All participants completed a task involving a 5-min baseline recording of HRV, followed by an emotional imagery task, during which their heart rate, skin conductance, and corrugator muscle responses were measured. Subjective ratings of emotional responses to imagery were also recorded. Results: No statistically significant differences in HRV were found between the anxiety and control groups. However, within the anxiety group, lower HRV was correlated with higher anxiety. Multivariate analysis of variance supported the hypothesis that greater physiological responses of anxious individuals to anxiety imagery, especially in the case of corrugator responses to generalized anxiety scenes, and skin conductance during relaxing intervals, were modified by baseline HRV levels. Compared to controls, anxious participants showed lower corrugator responses to specific anxiety scenes when their HRV was high. Subjective responses to imagery were also affected by HRV. Conclusions: The findings are consistent with prior literature and suggest that, even in community samples with high anxiety, high HRV is related to better emotion regulation and helps normalize anxious responses to threatening situations.